TOP Talent (USA Gymnastics, 2011)
USA Gymnastics' Talent Opportunity Program (TOPs) is in its 19th season and is still going strong. Fifty-four athletes participated in the three-day National TOPs Team Camp at the Women's National Team Training Center, held at the Karolyi Ranch in Huntsville, Texas, Dec. 1-5. An additional 58 athletes participated in the TOPs B Camp, Dec. 5-9. For the first time in the program's history, 8-year-old gymnasts participated in the training camps with tremendous success. The athletes were inspected in all four Olympic events and dance by the National Team Developmental Coaching staff. Lectures were also given by the staff to the coaches on training techniques. During the months of June and July, 2,800 gymnasts ages 7-11 were evaluated on physical abilities at the state level. From there the top 7 year olds were named to the Diamond Level team. The best 280 8-11 year old athletes were invited to participate in the National TOPs Testing in October, where they were evaluated on the same physical abilities tests and basic gymnastics skills. From National TOPs Testing, 54 athletes were named to the TOPs National Team and invited to participate in the National TOPs Training Camp in December. Former TOPs athletes indude Carly Patterson, Chellsie Memmel, Courtney Kupets, Tasha Schwikert, Alicia Sacramone and Samantha Peszek, just to name a few. Gary Warren, the USA Gymnastics Elite Program Director who oversees the TOPs program, said, "The training camps were, without a doubt, the most productive camps in our 19 years of existence and the indusion of the 8-year-old athletes was a tremendous success".